Hydrogel as an alternative to agar for laboratory rearing of the green peach aphid Myzus persicae - Ana Paula Nascimento Silva; Camila Faria Chagas; Emanuel Lucas de Andrade Alves; Vinícius de Castro Carvalho; Khalid Haddi (CABI Agriculture and Bioscience)
Abstract Background Rearing methodologies are critical for successful insect production. In this context, standard laboratory rearing of aphid species, like the green peach aphid Myzus persicae, uses plant leaf disks floating on an agar layer. However, agar is costly and its use in insect rearing is not always cost-effective. Here, the synthetic polymer hydrogel was tested as an affordable alternative for laboratory rearing of the green peach aphid. Methods Initially, the effects of three concentrations of hydrogel (0.3, 0.6, and 0.9 g per 100 ml) and agar (1 g per 100 ml) on the ability of aphids to complete their life cycle were compared. Then, using age-stage, two-sex life tables, the suitability of the hydrogel (0.6 g) as a substrate for two different host plants (e.i; Brassica oleraceae and Nicandra physalodes) under two different temperatures in aphids’ production was assessed. Subsequently, the response of the produced aphids in toxicological bioassays was tested. Results The hydrogel concentration of 0.6 g allowed the production of aphids in high numbers, similarly to the agar (1 g), without affecting their life cycle parameters or their reproductive outputs. Furthermore, the most significant differences between the evaluated treatments resulted mostly from the combined effects of the host plants and the temperatures. Therefore, colonies of M. persicae can be maintained over time producing sufficient offspring using N. physalodes leaves on a layer of hydrogel (0.6 g) at 20 °C. Moreover, in toxicological bioassays, the use of higher hydrogel concentrations (0.9 g) is recommended. Conclusions The hydrogel can be adopted as a viable alternative to replacing the widely used agar-based methodology for the green peach aphid rearing.